Analisis Strategi Memberdayakan Sumber Daya Manusia dalam Meningkatkan Kinerja Perguruan Tamansiswa Pematangsiantar - Nurhasanah Nurhasanah (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This study aims to describe the leadership of universities in increasing the participation of HR performance. In making decisions, it is necessary to involve human resources in the formulation of school development. School readiness in the field of human resources, facilities, equipment and external conditions owned by universities determines the target indicators of success. In developing the quality of universities by implementing policy strategies that include effective involvement and communication of all school components. The school's vision and mission are built based on an agreement reached by input from all components, including stakeholders. This research is qualitative research. The research site is at the Taman Siswa College, Pematang Siantar Branch. Research resource people are university administrators, school principals, vice principals, and teachers. Collecting data using observations, interviews and documentation. The validity of the data is checked using triangulation with the source. Data analysis techniques by means of data editing, data presentation and drawing conclusions and verification.